INCORPORATING INTERACTIVE ACTIVITIES IN TEACHING YOUNG LEARNERS (Academicia Globe: Inderscience Research, 2023)
In this article, the creative approach of the innovative activity-pedagogue to mastering the existing forms and tools for improving his profession is considered, and the classifications of stable and generally accepted scientific ideas about innovative activity in education and stable and universally accepted scientific ideas about innovative pedagogical activity are not yet fully formed. there is talk about the necessity of recognition.